2019
DOI: 10.1002/andp.201800381
|View full text |Cite
|
Sign up to set email alerts
|

Improving Our Knowledge on the 229mThorium Isomer: Toward a Test Bench for Time Variations of Fundamental Constants

Abstract: For more than four decades, the lowest excitation in the whole landscape of atomic nuclei, the low-lying, isomeric state of 229 Th, the so-called thorium isomer, has challenged physicists of various disciplines. Being a solitaire with its uniquely low excitation energy of <10 eV, its predicted lifetime of a few hours results in an extremely sharp relative linewidth E/E as low as 10 -20 . While until recently the indication of its existence was based only on indirect evidence, its unique properties inspired a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 96 publications
(166 reference statements)
0
17
0
Order By: Relevance
“…In the following, several applications will be considered in more detail. A thorough discussion of potential applications for a nuclear clock was provided in [349].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…In the following, several applications will be considered in more detail. A thorough discussion of potential applications for a nuclear clock was provided in [349].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…(9) andĤ 0 I as well asĤ 0 † I were used as defined in Eq. (12). Next the Lindblad superoperator L[ρ] is considered, which is the second term on the right-hand side of Eq.…”
Section: The Optical Bloch Equations For a Two-level Systemmentioning
confidence: 99%
“…Further, it will advance the field of experimental nuclear quantum optics [7][8][9]. With an expected accuracy of 1.5 • 10 −19 [3] a nuclear optical clock may even surpass the best optical atomic clocks operational today [10,11], having the potential for utilization in, e.g., satellite-based navigation [12], relativistic geodesy [13], probing for timevariations of fundamental constants [14] and the search for topological dark matter [15]. Two different concepts of nuclear laser excitation have to be distinguished: direct excitation and excitation via the inverse electronic bridge (IEB) mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The 229 Th 3+ system is also attractive from several technical perspectives [33], design and simulation work has shown that a trapped Th 3+ ion could be developed in a compact and relatively low-cost package, making field deployment in a dispersed network achievable. In addition, the 229 Th nucleus is expected to be an excellent system for the search for time variation of fundamental constants [34][35][36]. To this date, a few groups worldwide have demonstrated thorium trapping in ion traps [37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%